THE APPLICATION OF THREE-STEP TO INCREASE THE STUDENTSâ SPEAKING ABILITY - Mallombasi, Andi (EXPOSURE JOURNAL, 2012)
This research was intended to explain the studentsâ speaking accuracy and fluency through Three-Step Interview Method in class XI-2 of SMA Negeri 2 Bantaeng in the 2011/2012 academic year. This research used A Classroom Action Research (CAR). It had conducted in two cycles; each cycle consisted of four meetings. The subjects of this research were students in class XI-2 involved 40 students. Those consisted of 30 women and 10 men. The researcher took real data from the class to know the studentsâ speaking ability. The instruments of this research were speaking test and observation sheet in cycle I and in cycle II. The research findings indicated that the Three-Step Interview Method improved the studentsâ speaking ability covered studentsâ accuracy and fluency in class XI-2 of SMA Negeri 2 Bantaeng. It was indicated that there was improvement of the studentsâ speaking ability from diagnostic test to cycle I and from that to cycle II. The studentsâ diagnostic test of speaking ability was (5.47) and after gave action by using three-step interview method indicated that there was improvement from diagnostic test to cycle I and from that to cycle II. The studentsâ speaking ability in cycle I was 63.00% and in cycle II become 76.50% and it was classified as good. While the standard target scores 70% one which was categorized good. From these findings, there was a significant improvement of the studentsâ speaking ability through Three-Step Interview Method. Based on the result finding the research concludes that Three-Step Interview Method can improve the studentsâ speaking ability.Keywords: Application, Three-Step, Increase, Speaking.Â Penelitian ini bertujuan untuk menjelaskan akurasi berbicara siswa dan kelancaran melalui Tiga Langkah Metode Wawancara di kelas XI-2 SMA Negeri 2 Bantaeng pada tahun akademik 2011/2012. Penelitian ini menggunakan sebuah Penelitian Tindakan Kelas (PTK). Hal itu dilakukan dalam dua siklus; setiap siklus terdiri dari empat pertemuan. Subyek penelitian ini adalah siswa kelas XI-2 melibatkan 40 siswa. Mereka terdiri dari 30 perempuan dan 10 laki-laki. Peneliti mengambil data ril dari kelas untuk mengetahui kemampuan berbicara siswa. Instrumen penelitian ini tes berbicara dan lembar observasi pada siklus I dan siklus II. Temuan penelitian menunjukkan bahwa Tiga Langkah Metode Wawancara meningkatkan kemampuan berbicara siswa yang mengarah pada akurasi siswa dan kelancaran dalam kelas XI-2 SMA Negeri 2 Bantaeng. Hal itu menunjukkan bahwa ada peningkatan kemampuan berbicara siswa dari tes diagnostik untuk siklus I dan dari siklus ke II. Tes diagnostik siswa dari kemampuan berbicara adalah (5.47) dan setelah diberikan tindakan dengan menggunakan metode wawancara tiga langkah menunjukkan bahwa ada perbaikan dari tes diagnostik untuk siklus I dan dari siklus yang ke II. Kemampuan siswa berbicara pada siklus I adalah 63, 00% dan pada siklus II menjadi 76, 50% dan itu tergolong baik. Sementara nilai sasaran standar 70% satu yang dikategorikan baik. Dari temuan ini, ada peningkatan yang signifikan dari kemampuan berbicara siswa melalui Tiga-Langkah Metode Wawancara. Berdasarkan hasil penelitian menemukan kesimpulan bahwa Metode Tiga Langkah Wawancara dapat meningkatkan kemampuan berbicara siswa.Kata Kunci: Aplikasi, Tiga-Langkah, Meningkatkan, Berbicara.